Assessment of Leisure Time Physical Activity and Brain Health in a Multiethnic Cohort of Older Adults - Gu, Yian (JAMA Netw Open, 2020)
IMPORTANCE: Results from longitudinal studies suggest that regular leisure time physical activity (LTPA) is associated with reduced risk of dementia or Alzheimer disease. Data on the association between LTPA and brain magnetic resonance imaging (MRI) measures remain scarce and inconsistent. OBJECTIVE: To examine the association of LTPA and MRI-assessed brain aging measures in a multiethnic elderly population. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study included 1443 older (≥65 years) adults without dementia who were participants of the Washington/Hamilton Heights-Inwood Columbia Aging Project study. LTPA, from self-reported questionnaire, was calculated as metabolic equivalent of energy expenditure. Both moderate to vigorous LTPA, assessed as meeting Physical Activity Guidelines for Americans (≥150 minutes/week) or not, and light-intensity LTPA were also examined. EXPOSURES: LTPA. MAIN OUTCOMES AND MEASURES: Primary outcomes included total brain volume (TBV), cortical thickness, and white matter hyperintensity volume, all derived from MRI scans with established methods and adjusted for intracranial volume when necessary. We examined the association of LTPA with these imaging markers using regression models adjusted for demographic, clinical, and vascular risk factors. RESULTS: The 1443 participants of the study had a mean (SD) age of 77.2 (6.4) years; 921 (63.8%) were women; 27.0%, 34.4%, and 36.3% were non-Hispanic White, non-Hispanic African American, and Hispanic individuals, respectively; and 27.3% carried the apolipoprotein E (APOE) ɛ4 allele. Compared with the LTPA of nonactive older adults, those with the most LTPA had larger (in cm(3)) TBV (β [SE], 13.17 [4.42] cm(3); P = .003; P for trend = .006) and greater cortical thickness (β [SE], 0.016 [0.008] mm; P = .05; P for trend = .03). The effect size comparing the highest LTPA level with the nonactive group was equivalent to approximately 3 to 4 years of aging (β for 1 year older, −3.06 and −0.005 for TBV and cortical thickness, respectively). A dose-response association was found and even the lowest LTPA level had benefits (eg, TBV: β [SE], 9.03 [4.26] cm(3); P = .03) compared with the nonactive group. Meeting Physical Activity Guidelines for Americans (TBV: β [SE], 18.82 [5.14] cm(3); P < .001) and light-intensity LTPA (TBV: β [SE], 9.26 [4.29] cm(3); P = .03) were also associated with larger brain measures. The association between LTPA and TBV was moderated by race/ethnicity, sex, and APOE status, but generally existed in all subgroups. The results remained similar after excluding participants with mild cognitive impairment. CONCLUSIONS AND RELEVANCE: In this study, more physical activity was associated with larger brain volume in older adults. Longitudinal studies are warranted to explore the potential role of physical activity in brain health among older individuals.